The Impact of Aluminum Doping on the Performance of MgV2O4 Spinel Cathodes for High-Rate Zinc-Ion Energy Storage - He Lin; Zhiwen Wang; Yu Zhang (Molecules, 2025)
This study explores the development of aluminum-doped MgV2O4 spinel cathodes for aqueous zinc-ion batteries (AZIBs), addressing the challenges of poor Zn2+ ion diffusion and structural instability. Al3+ ions were pre-inserted into the spinel structure using a sol-gel method, which enhanced the material’s structural stability and electrical conductivity. The doping of Al3+ mitigates the electrostatic interactions between Zn2+ ions and the cathode, thereby improving ion diffusion and facilitating efficient charge/discharge processes. While pseudocapacitive behavior plays a dominant role in fast charge storage, the diffusion of Zn2+ within the bulk material remains crucial for long-term performance and stability. Our findings demonstrate that Al-MgV2O4 exhibits enhanced Zn2+ diffusion kinetics and robust structural integrity under high-rate cycling conditions, contributing to its high electrochemical performance. The Al-MgVO cathode retains a capacity of 254.3 mAh g−1 at a high current density of 10 A g−1 after 1000 cycles (93.6% retention), and 186.8 mAh g−1 at 20 A g−1 after 2000 cycles (90.2% retention). These improvements, driven by enhanced bulk diffusion and the stabilization of the crystal framework through Al3+ doping, make it a promising candidate for high-rate energy storage applications.